Enhancing Employee Performance Through Communication and Transformational Leadership: A Mediation Study on Job Satisfaction at the East Java Province Plantation Service - Pudjowati, Juliani; Mas'adah, Mas'adah (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This research seeks to examine the influence of communication, transformational leadership, and work satisfaction on staff performance in the East Java Provincial Plantation Service. Furthermore, it analyzes the correlation among communication, transformational leadership, and job satisfaction to comprehend their impact on workplace dynamics.Methodolog: A quantitative methodology was used, with data gathered via surveys administered to 117 workers, selected using a total sampling method. Path analysis was used to elucidate the links among the examined variables, facilitating a thorough comprehension of the direct and indirect influences of communication and leadership on work satisfaction and employee performance.Findings:The results indicate that communication and transformational leadership significantly influence employee performance. Job satisfaction is also positively correlated with performance, meaning that employees who experience higher job satisfaction tend to perform better. Additionally, communication and transformational leadership have a strong impact on job satisfaction, suggesting that effective communication and inspirational leadership styles enhance overall employee satisfaction.Conclusion:This study underscores the crucial role of communication and transformational leadership in improving both job satisfaction and employee performance. In government institutions like the East Java Provincial Plantation Service, fostering a culture of open communication and strong leadership can lead to a more motivated and productive workforce. The findings suggest that prioritizing these elements can enhance organizational effectiveness and contribute to institutional success.